Towards situated histories of heterogenous infrastructures: Oral history as method and meaning. Issue 134 (August 2022) - Ernstson, Henrik; Nilsson, David
Highlights: Plain life stories can unpack complex histories of infrastructure in Southern cities. Provides historical accounts of how formal/informal infrastructure systems interact. Infrastructure is shown to emerge as part of situated everyday relations. Oral history provides an important method to understand heterogenous infrastructure. Abstract: Building on interviews with elderly people living in a low-income and auto-constructed settlement in Kampala, Uganda, this paper explores the notion of heterogenous infrastructure in its local spatial and temporal setting. Our aim is twofold. First, by intently listening to and weaving together situated narratives of how people over time have acquired infrastructural services, such as water, energy, waste, and sanitation, we reveal deeper insights of the socio-political, but also material structures and interactions at play between the State, the disenfranchised, and their intermediaries. Second, we start uncovering the so far largely unexplored potential of oral history as a method to meaningfully interpret the "infrastructural past" of postcolonial and Southern cities where most of ordinary people's experience was never put on record. Our findings point to the usefulness of oral history methods to widen the lens of who and what contributed to the production of fundamental resources for urban life—and its politics.